Perceptions of South African plastic surgeons regarding academic education in the field of cleft lip and palate - Emad Ghabrial; Anil Madaree (Wolters Kluwer Medknow Publications, 2024)
Background: Historically, South African plastic surgeons (PSs) have been managing cleft lip/palate (CLP) and craniofacial anomalies (CA). PS lead CL/P teams globally where the need arises. The complex, lengthy nature of CL/P management requires holistic services and collaboration between disciplines. Academic education should provide in-depth knowledge, interdisciplinary participation, and clinical exposure to field experts. Objectives: An investigation into exposure and knowledge of South African PS regarding management of CL/P. An opinion from practicing PS about academic educational needs for working with CL/P patients. Methods: Online survey and telephone interviews (a structured questionnaire) investigating opinions of PS in CL/P to determine satisfaction with the adequacy of academic education and perceived needs. Results: The questionnaire was completed by 41% of practicing PS from Medpages health-care provider database. Most respondents (63.3%) were between 30 and 49. Of them, 74% showed good general knowledge of CL/P. However, 76.5% acknowledged limited clinical training and exposure in this field, preventing them from adequate services provision to CL/P patients. Only 41% offered primary and/or secondary treatment to CL/P patients and 40% had participated in interdisciplinary teams. All agreed on the need for a dedicated training program(s) in CL/P management. The majority recommended subspeciality training through a clinical fellowship or a degree course. Conclusion: PS postgraduate academic training and clinical exposure are limited in the CL/P field. An educational strategy should be established to meet the needs of PS providing CL/P care. Part-time clinical fellowship and/or degree courses would prepare them adequately for a career managing CL/P and CA patients.